Bentonite/hydroxyethylcellulose as eco-dielectrics with potential utilization in energy storage - Barzic Andreea Irina; Stoica Iuliana; Asandulesa Mihai; Albu Raluca Marinica; Oprisan Bogdan (e-Polymers, 2023)
This study deals with the preparation and characterization of novel composites accomplished by filling hydroxyethylcellulose with several amounts of bentonite. Molecular modeling enabled understanding the conformational and physicochemical features, which are responsible for the chemical reactivity parameters. Rheological analyses are made to investigate the effect of the polymer loading on the shear flow behavior. The morphology and homogeneity of each system is explored via optical microscopy. The band gap of the samples is slightly reduced by the addition of the bio-filler in the cellulosic medium, as indicated by UV-VIS spectral data. The dielectric response of these materials is extracted from refractometry experiments at several wavelengths. The electric energy density was achieved based on the dielectric properties determined at high and low frequencies. The outcome of this study offers new ways to produce alternative dielectric eco-materials having a good potential of accumulating electrical energy, as demanded for capacitor devices.